Sosialisasi Perlindungan Hukum Terhadap Kepemilikan Tanah bagi Masyarakat Desa Mersam - Baidawi, Ahmad; Dewi, Ratna; Abdi Muhammad, Hatta (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
Land is a very important factor in the lives of Indonesian people, especially in rural communities where most of the population depends on land for their livelihood. The purpose of this community service program is to provide understanding through socialization activities to the Mersam village community about the importance of having land ownership certificates, as well as the importance of understanding legal land ownership and environmental conservation. The target audience for this community service initiative includes village officials, the Mersam community, and invited guests in general. The methods used in this initiative include socialization, training, and simulations. In the socialization, training, and simulation methods, various approaches are employed, such as lectures, question-and-answer sessions, and discussions. The ultimate goal of this community service is to enhance the understanding of the Mersam community regarding the importance of legal land ownership, the importance of having a land ownership certificate (SHM), and increased knowledge about environmental conservation, as well as fostering awareness among the community to maintain environmental cleanliness and have green open spaces. Keywords: Socialization; Land Ownership; Law; Mersam Village